INVESTIGATING EFL STUDENTSâ LISTENING ANXIETY: A SURVEY AT UIN ANTASARI BANJARMASIN - Maulidiyah, Noor (English Department of Faculty of Tarbiyah and Teachers Training, 2017)
Listening anxiety is an influential factor that obstructs the EFL learnersâ listening comprehension.Â This research is conducted to find out the levels of listening anxiety of the third semester students of English department at Tarbiyah and Teachers Training faculty of Antasari State Islamic University.Â The research aims to answer two research questions: (1) Do the students who have sufficient and low ability in listening experience listening anxiety? And (2) which item measured in the Foreign Language Listening Anxiety Scale do EFL learners face the most and least anxiety?Â This descriptive quantitative research took 88 students as participants in this research.Â The researcher used questionnaire for collecting the data.Â The findings show that the students do experience high level of listening anxiety.Â The students responded to 16 items which indicted high level of listening anxiety.Â The item that indicated the highest level of listening anxiety was included in background knowledge component and the item that indicated the lowest level of listening anxiety was included in listening text and strategies component.Â However, among three themes of items, most of students responded to items indicating high level of listening anxiety were in listening text and strategies component.Â Â